Access to sanitation and risk of developing urinary tract infections among women from low socio-economic settings - Kawade, Rama; Radkar, Anjali; Thadathil, Abhilash; Thakur, Deepa (International Journal Of Community Medicine And Public Health, 2019)
Background: Poor sanitation facilities are root cause of many health problems of people residing in slums. The present study estimates the prevalence of urinary tract infections (UTI) and identifies factors associated with an increased risk of UTI among women. Methods: A cross-sectional study was conducted among 616 women aged between 18 to 60 years residing in 33 slums across four cities in Maharashtra, India. Data related to individual characteristics of women, housing condition, access to sanitation facilities, behaviors adopted by the women that could lead to UTI and an episode of symptomatic UTI in the previous one month were recorded through structured questionnaire. Logistic regression analysis was performed to find out risk factors for UTI among women. Results: The prevalence of UTI was found to be 19.6%. The prevalence was higher among young women aged upto 30 years (23.2%). In absence of individual toilet, women had adopted certain behaviors such as urine holding (21.3%), modify dinner to avoid toilet use at night (26.6%) and avoid intake of liquids (10.7%) to reduce frequency of visits to toilet. All these behaviors were significantly associated with UTI. Multiple logistic regression indicated that UTI was strongly and independently associated with age (OR=1.64, 95%CI: 1.08, 2.47), no access to bathroom (OR=2.21, 95%CI: 1.08, 4.49) and avoid intake of liquids (OR=2.70, 95%CI: 1.53, 4.75) (p<0.05). Conclusions:Behavior modifications by women to adjust with restricted use of place of urination may affect their health and increase the likelihood of developing UTI. Younger women are more at risk of developing UTI.